Removal of chromium from wastewater by adsorption and by biosorption - Tavares, M. T. (1996)
The objective of this work is the definition of an efficient biosorption system based on the ability of some microorganisms, metabolica1ly active or not, to retain heavy metals, specially the hexavalent fonn of Cr. Metallic solutions were passed through mini-colunms in which a biotilm was developed at pre-established conditions. As industrial wastewater usually contains organic and inorganic compounds, besides metallic ions, it would be desirable to co-extract several pollutants at the same time. The utilization of granular activated carbon (GAC) as a support for the biofilm seems to be advantageous, as it can retain other substances while the biofilm removes the heavy metal. To quantify the contribution of GAC to the overall removal of chromium, adsorption studies were carried out with the determination the effect of pH and of the presence of concurrent species on the adsorption isotherms. Biosorption studies were done with three different bacteria, Pseudomonasjluorescens, Escherichia coli and Arthrobacter viscosus. Among microorganisms, bacteria are particularly interesting for the purpose as they are able to excrete polysaccharides allowing a good adhesion to the support, implementing the retention capacity of the biosystem and protecting the cells from the xenobiotic effect of the heavy metal ions. Removal efficiencies were compared between the three biosystems.